Impact of Prior Antiplatelet Therapy on Outcomes After Endovascular Therapy for Acute Stroke: Endovascular Treatment in Ischemic Stroke Registry Results. Issue 12 (20th September 2021) - Couture, Marie; Finitsis, Stephanos; Marnat, Gaultier; Richard, Sébastien; Bourcier, Romain; Constant-dits-Beaufils, Pacôme; Dargazanli, Cyril; Arquizan, Caroline; Mazighi, Mikaël; Blanc, Raphaël; Eugène, François; Vannier, Stéphane; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: The influence of prior antiplatelet therapy (APT) uses on the outcomes of patients with acute ischemic stroke treated with endovascular therapy is unclear. We compared procedural and clinical outcomes of endovascular therapy in patients on APT or not before stroke onset. Methods: We analyzed 2 groups from the ongoing prospective multicenter Endovascular Treatment in Ischemic Stroke registry in France: patients on prior APT (APT+) and patients without prior APT (APT−) treated by endovascular therapy, with and without intravenous thrombolysis. Multilevel mixed-effects logistic models including center as random effect were used to compare angiographic (rates of reperfusion at the end of procedure, procedural complications) and clinical (favorable and excellent outcome, 90-day all-cause mortality, and hemorrhagic complications) outcomes according to APT subgroups. Comparisons were adjusted for prespecified confounders (age, admission National Institutes of Health Stroke Scale score, Alberta Stroke Program Early CT Score, intravenous thrombolysis, and time from onset to puncture), as well as for meaningful baseline between-group differences. Results: A total of 2939 patients were analyzed, of whom 877 (29.8%) were on prior APT. Patients with prior APT were older, had more frequent vascular risk factors, cardioembolic stroke mechanism, and prestroke disability. Rates of complete reperfusion (37.9% in the APT− group versus 42.7 % in the APT+ group; aOR, 1.09 [95% CI, 0.88–1.34]; P =0.41) and periprocedural complication (16.9% versus 13.3%; aOR, 0.90 [95% CI, 0.7–1.2]; P =0.66) did not differ between the two groups. Symptomatic intracerebral hemorrhage (aOR, 0.93 [95% CI, 0.63–1.37]; P =0.73), 3 months favorable clinical outcome (modified Rankin Scale score of 0–2; aOR, 0.98 [95% CI, 0.77–1.25]; P =0.89), and mortality (aOR, 0.95 [95% CI, 0.72–1.26]; P =0.76) at 90 days did not differ between the groups. Conclusions: Prior APT does not influence angiographic and functional outcomes following endovascular therapy and should not be taken into account for acute revascularization strategies.